Diagnostic value of combined detection of serum cystatin C and β2-microglobulin for hypertensive nephropathy - YU Yao; ZHANG Chun-min; HUANG Xue-mei; GUO Bian-qin (Linchuang shenzangbing zazhi)
Objective To study the clinical value of combined detection of serum cystatin C andβ2-microglobulin in the diagnosis of hypertensive nephropathy.Methods 228 hypertensive patients and51 normal controls from Jan.2013 to Oct.2014 were selected.According to the glomerular filtration rate calculated by the simplified MDRD formula,228 hypertensive patients were divided into four groups:group A(simple hypertension),group B(hypertensive nephropathy of stage Ⅰ),group C(hypertensive nephropathy of stage Ⅱ),and group D(hypertensive nephropathy of stage Ⅲ-Ⅳ).The serum levels of Cys C,β2-MG and SCr were determined and compared among the groups.Results There was no significant difference in the serum-levels of Cys C,β2-MG and SCr between control group and group A.The serum levels of Cys C and β2-MG were increased in groups B,C and D as compared with control group(P<0.01).The serum SCr level showed no significant difference between control group and group B,but higher in groups C and D than in control group(P<0.01).The serum levels of Cys C,β2-MG and SCr showed a rising trend with the severity of hypertensive nephropathy.ROC curves showed that the AUC of Cys C,β2-MG and SCr in hypertensive nephropathy patients was0.879,0.881 and 0.967 respectively.In each group,the positive rate of the combined detection of three indicators was higher than that of the combined detection of Cys C and β2-MG,and the positive rate was higher than that of single detection.Correlation analysis showed a negative correlation between GFR and Cys C,β2-MG,SCr with the correlation coefficient being-0.776,-0.742,and-0.732 respectively(P<0.01).There was strong better correlation between Cys C and β2-MG with the correlation coefficient being 0.912(P<0.01).Conclusions The serum levels of Cys C and β2-MG could be used as important indicators to judge hypertensive nephropathy.Combined detection of Cys C and β2-MG could improve the sensitivity of the diagnosis for early hypertensive nephropathy,and it was an important clinical value to diagnose and treat hypertensive nephropathy accurately through combined determination of the serum levels of Cys C,β2-MG and SCr regularly.